2022
DOI: 10.1038/s41598-022-25482-x
|View full text |Cite
|
Sign up to set email alerts
|

Fungivorous mites enhance the survivorship and development of stingless bees even when exposed to pesticides

Abstract: Stingless bees are the largest group of eusocial bees in the world. They play an essential role as crop pollinators and have been considered for inclusion in pesticide risk assessments (RAs). Beyond the mutualism involving stingless bee larvae and fungi, the fungivorous mite Proctotydaeus (Neotydeolus) alvearii proved to be interesting for studies of associations with stingless bees. Their presence is related to colony strength and health, showing a permanent-host-association level. Here, we tested whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…SDCP2 through the production of lovastatin and monascin, respectively ( Paludo et al, 2019 ). More recently, Rosa-Fontana et al (2022) reported the presence of fungivorous mites in brood cells of the Scaptotrigona postica , which might be involved in controlling the multiplication of both mutualistic and opportunistic fungi in the brood cell favoring the larval development of this SB.…”
Section: Introductionmentioning
confidence: 99%
“…SDCP2 through the production of lovastatin and monascin, respectively ( Paludo et al, 2019 ). More recently, Rosa-Fontana et al (2022) reported the presence of fungivorous mites in brood cells of the Scaptotrigona postica , which might be involved in controlling the multiplication of both mutualistic and opportunistic fungi in the brood cell favoring the larval development of this SB.…”
Section: Introductionmentioning
confidence: 99%